Removal of paracetamol from aqueous solution by wood sawdust-derived activated carbon: Process optimization using response surface methodology - Tunc, Muslun Sara; Yildiz, Burcin; Tasar, Seyda (Taylor & Francis Inc, 2022)
The removal of paracetamol pharmaceutical from the aqueous solution by activated carbon prepared from wood sawdust (WSAC) was studied in the current research. The Response Surface Methodology (RSM) was used to model WSAC paracetamol removal, optimize operational parameters, and determine the impact of operational parameters such as adsorbent dosage, initial concentration of paracetamol, and contact time. According to the results of variance analysis (ANOVA), the quadratic model was statistically significant (P < 0.0001), and the determination coefficient value (R-2=0.9847) was high. The high determination coefficient value of the quadratic model indicated that the experimental results adapted well with the predicted results, that is, the model was valid for envisaging the experimental results. The optimum conditions were obtained to be 0.16 g/100 mL WSAC dosage, 11.52 mg/L initial paracetamol concentration, and 90.52 min contact time by the desirability function, resulting in the paracetamol removal of 99.24%. The results of the isotherm studies indicated that the isotherm equations of Langmuir, Temkin, and Dubinin all fit the paracetamol adsorption data. The maximum adsorption capacity (q(max)) of WSAC was calculated as 15.90 mg/g using the Langmuir isotherm equation. Kinetic study results revealed that the pseudo-second-order kinetic model adapted well to the paracetamol adsorption data.
Keywords: Adsorption; adsorption isotherms and kinetics; characterization; pharmaceuticals removal; response surface methodology; variance analysis (ANOVA)